Alterations in the gut microbiota and the efficacy of adjuvant probiotic therapy in liver cirrhosis - Wu, Zengrong; Zhou, Hejun; Liu, Deliang; Deng, Feihong (Frontiers in Cellular and Infection Microbiology, 2023)
Background Liver cirrhosis is the end stage of various chronic liver diseases (CLDs). The gut microbiota can impact the liver environment and trigger chronic liver inflammation through the gut-liver axis. Alteration of the gut microbiota has become an effective strategy in the biological treatment of cirrhosis. Methods Twenty-eight patients with liver cirrhosis and 16 healthy individuals were included, and fresh stool samples were collected. We analyzed changes in the gut microbiota between groups by 16S rRNA sequencing and evaluated the association between microbiota alterations and hepatic function. Additionally, 102 cirrhotic patients were retrospectively enrolled and divided into a probiotic group (n=44) and a nonprobiotic group (n=58) in addition to standard treatment for cirrhosis. Patients were monitored for hematological parameters and hepatic function during the six-month follow-up. Results The gut microbiota profile of patients with cirrhosis was greatly different from that of healthy individuals, presenting with significantly reduced α diversity and decreased abundance of representative SCFA-producing bacteria including Firmicutes, Coprococcus and Clostridium IV. The pathogenic bacteria Gammaproteobacteria, Veillonella, and Bacilli were greatly enriched in cirrhotic patients. Additionally, patients with decompensated cirrhosis (DCPC) had a significantly reduced abundance of Oscillibacter compared to compensated cirrhosis (CPC), which is also a SCFA-producing bacteria, and the lower Firmicutes to Bacteroidetes ratio and enhanced MDR values were also shown in DCPC patients compared to CPC patients. In addition, the abundance of Firmicutes was negatively related to hepatic function in cirrhotic patients, including the levels of ALT, AST, and DBIL. From the retrospective study, we found that biochemical improvements in alanine transaminase (ALT) and total bilirubin (TBIL) were obtained in DCPC patients who received oral probiotic therapy compared with the nonprobiotic group. Conclusion Severe microbial dysbiosis existed in patients with liver cirrhosis, especially patients who reached the decompensatory stage. SCFA-producing bacteria were significantly reduced in cirrhosis. Altered gut microbiota cause changes in functional modules, which may contribute to cirrhosis progression and are associated with clinical prognosis. Adjuvant probiotic supplementation to enhance SCFA-producing bacteria can be a prospective therapy for patients with cirrhosis.